Os direitos de aprendizagem do eixo estruturante produção de textos escritos na prática do professor participante do PNAIC - Dantas, Jaciara de Lira Almeida (2019)
Writing is historically recognized as an activity whose function is to share our way of thinking about the affairs of a culture or society. Current studies in education, linguistics and psychology are consensual in order to recognize the need to lead a child to reflect on the function and use of the alphabetic writing system, as well as to insert it in literacy practices and situations written production. Therefore, this study aims to identify teaching practices that value writing as a skill in use in society and contribute to the autonomy and proficiency of student writing. And as specific objectives, to know the teacher's understanding of the learning rights and their conception of writing; observe practices in the classroom; describe and analyze the data using as a parameter one of the axes of the MEC document, the axis of production of written texts. Methodologically, it was listed a field research with descriptive and exploratory character and qualitative methodology, which allowed us to know, observe and systematically describe teaching practices developed by a teacher participating in the National Pact for Literacy in the Right Age - Pacto Nacional pela Alfabetização na Idade Certa or PNAIC in Portuguese - from a class of the third year of Elementary School. The corpus consisted of 20 visits to the school, held in a period of four months and gathered information collected in interviews and observations of practices on written production in the classroom. Theoretically we relied on the conception of socially constructed language based on Vygotsky (1991), Bakhtin (1995), Tfouni (2010), Kleiman (2002), Soares (2004), Marcuschi (2008), among other researchers of the theme. From the analysis of the corpus it is possible to conclude that there is a coherence between the content presented in the interview and the practices observed in the classroom and that the Learning Rights of the axis of the Production of texts are instituted in the classroom through practices experienced by the children. We also noted that the teacher shows constant concern with the notational writing system and that to follow the progression of the students it establishes a systematic routine of individual and collective interaction that challenges students to reflect, question and test different hypotheses in their textual productions. This teaching perspective has allowed us to understand that the teacher has been assuring students the right to learn to plan, produce and organize a written text. Thus, we hope that this research can contribute to the academic community, foster new discussions and share good writing practice.